Diversity and Resistance to Thiophanate-Methyl of Colletotrichum spp. in Strawberry Nursery and the Development of Rapid Detection Using LAMP Method - Jianyan Wu; Shuodan Hu; Boyang Ye; Xiaoran Hu; Wenfei Xiao; Hong Yu; Chuanqing Zhang (Agronomy, 2022)
Anthracnose is a devastating fungal disease in strawberry nurseries. Multiple Colletotrichum species are responsible for strawberry anthracnose. In this study, 105 Colletotrichum isolates were obtained from strawberry seedlings with anthracnose symptoms in fifteen nurseries located in Zhejiang province, China, and were classified based on multilocus sequence and morphological characteristic analyses. Analysis of ITS, ACT, CAL, CHS-1, and GAPDH revealed that four species within C. gloeosporioides species complex, including C. siamense (56 isolates, 53.3%), C. fructicola (37 isolates, 35.2%), C. gloeosporioides (7 isolates, 6.7%), and C. aenigma (5 isolates, 4.8%), were detected in diseased seedlings. Thiophanate-methyl is one of the benzimidazole fungicides, and has long been used to control strawberry anthracnose in China. Here, thiophanate-methyl resistance of Colletotrichum isolates was determined by the minimum inhibitory concentration (MIC) method. Our results indicated that the resistance frequency was up to 96.2%, containing 94.3% of highly resistant isolates. Only four sensitive isolates (two C. fructicola, one C. gloeosporioides, and one C. siamense isolates) and two moderately resistant isolates (one C. aenigma isolate and one C. siamense isolate) were detected. Our data indicated that the high resistance was mainly caused by the E198A mutation in the β-tubulin protein. In addition, F200Y (TTC→TAC) in the β-tubulin protein were detected in two moderately resistant isolates. Based on the point mutation at codon 198 (GAG→GCG) in the β-tubulin gene of Colletotrichum isolates, we developed a loop-mediated isothermal amplification (LAMP) assay to rapidly detect the E198A mutants. Collectively, our study indicated that four species within the C. gloeosporioides species complex were associated with anthracnose symptoms in strawberry nurseries in Zhejiang province, and serious resistance was widespread in each Colletotrichum species.